2013
DOI: 10.1080/21553769.2013.876451
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hypertension induces alterations in immunological factors of colostrum and human milk

Abstract: The aim of this study was to evaluate the changes in minerals, antibodies, complement and cytokine levels in the human milk of hypertensive women based on the time of collection (diurnal/nocturnal) and the type of milk. The material was collected from 23 mothers at three stages of maturity: 3 days (colostrum), 10 days (transitional milk) and 30 days (mature milk) postpartum -and at two times -diurnal (12:00 h) and nocturnal (24:00 h) -resulting in a total of 138 samples. The minerals, antibody, complement, IFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…Concerning the morbidities, nine papers evaluated diabetes mellitus [8][9][10][11][12][13][14][15][16][17] , one evaluated hypertension 18 and four overweight 17,[19][20][21] . Only one paper evaluated both diabetes and overweight ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Concerning the morbidities, nine papers evaluated diabetes mellitus [8][9][10][11][12][13][14][15][16][17] , one evaluated hypertension 18 and four overweight 17,[19][20][21] . Only one paper evaluated both diabetes and overweight ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The main results were: 1) three papers that evaluated the nutritional composition of human milk of women with diabetes mellitus found a lower concentration of lactose 10,11,15 , and four of fat 9,12,13,16 . Concerning hypertension, a higher total protein concentration was found in both colostrum and mature milk 18 . In the case of overweight, half of the studies observed a higher fat and energy content in the milk of these mothers 17,20 .…”
Section: Not Informedmentioning
confidence: 94%
See 2 more Smart Citations
“…The scientific data concerning human milk glycomics in relation to maternal disease is fragmentary. However, it was reported that diabetes mellitus [72][73][74], overweight [75,76] or hypertension [77] of the lactating mother has an impact on the nutritional composition of milk. A summary of the main trends observed in the nutritional composition of mother's milk was presented by Amaral and coworkers [78] as well as the systematic review by Peila and coworkers [79].…”
Section: Maternal Morbidities and Their Impact On Fucosylation Of Diementioning
confidence: 99%